"Good women do not inherit land" : politics of land and gender in India - Rao, Nitya (Social Science Press : Distributed by Orient Blackswan, 2012)
Study on the rights of Santal women in Dumka District of Jharkhand.GOOD WOMEN should not claim a share in the inheritance, even if they have no brothers.... Notions such as this have, in their own way and over time, given the women in the Santal Parganas the resolve to wrest what is rightfully theirs. This is a powerful book in the way in which it unfolds the lives and anxieties of Santal women in the two villages of Dumka district, Jharkhand. From the very beginning, adivasi women come alive through separate life histories. They span different situations and social patterns but all of them relate to rights in landed property, and their own troubled identities in the backdrop of harsh living conditions, social discrimination and lack of state support. Land for the Santal women is not a mere economic resource. It stands for security, social position and identity, and in this men have a distinct advantage. Soon after, writing in a personal vein, the author unfolds how these anxieties of the Santal women resonate her own. The author traces the relationship between Santals and their land from historic times to the modern era when they have access to both the modern legal system and their own customary laws. She also examines the role of external agencies in this struggle government administrative bodies, non-governmental organizations and political leaders. As modern influences crowd out traditional mores the author asserts that development is not always a benign process of social advancement but a highly political struggle for re-negotiating power relations between men and women, and among social groups. The use of a community identity as adivasis has also been responsible for denying women rights to land in the context of the movement for political autonomy of Jharkhand. Based on rich ethnographic material, this sensitive book lays bare the reality of being an adivasi and an adivasi woman, in all its nuances, in the modern globalized world